Central Asia After the Empire - Kulchik, Yuriy; Fadin, Andrey and Sergeev, Victor; Foreword By Fred Halliday (London Pluto Press, 1996)
The Central Asian republics of the former Soviet Union gained autonomy in 1991. Hidden from the West for so long, little is known about Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. Now, in the Post-Cold War era, the shifts of power taking place within these oil-rich republics will be keenly observed by the West and by neighbouring economies such as China, Turkey and Iran.
Inclde Index, Biliography, Notes, Appendix and Map
Keywords: Asia, Central -- History -- 1991- -- Diplomatic R`elations